2018
DOI: 10.3390/ijms19030696
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vitis amurensis VaERF20 in Arabidopsis thaliana Improves Resistance to Botrytis cinerea and Pseudomonas syringae pv. Tomato DC3000

Abstract: Ethylene response factor (ERF) transcription factors play important roles in regulating immune responses in plants. In our study, we characterized a member of the ERF transcription factor family, VaERF20, from the Chinese wild Vitis genotype, V. amurensis Rupr “Shuangyou”. Phylogenetic analysis indicated that VaERF20 belongs to group IXc of the ERF family, in which many members are known to contribute to fighting pathogen infection. Consistent with this, expression of VaERF20 was induced by treatment with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…MgCl 2 (10 mM) was used for mock inoculation. Samples were collected 18 h later, and stained with aniline blue as described by Wang et al [61].…”
Section: Methodsmentioning
confidence: 99%
“…MgCl 2 (10 mM) was used for mock inoculation. Samples were collected 18 h later, and stained with aniline blue as described by Wang et al [61].…”
Section: Methodsmentioning
confidence: 99%
“…For example, expression profiling of grape VvERF showed that it was highly expressed in response to Botrytis cinerea infection [103]. Also, transgenic Arabidopsis overexpressing the VaERF20 gene from Amur grape had enhanced resistance to Pseudomonas syringae and Botrytis cinerea pathogens [104].…”
Section: Erf/dreb Tfsmentioning
confidence: 99%
“…In addition, it was reported that elevated expression of VaERF20 in grape increased resistance to B. cinerea and Pseudomonas syringae (Wang et al . ).…”
Section: Introductionmentioning
confidence: 97%